Assessing Speaking Skill in English Language Teaching and Learning - Supriusman Supriusman (International Conference on Languages and Arts, 2012)
The ability to assess speaking in English language teaching is very important for English teachers because as one of language productive skills, speaking cannot be assessed directly and objectively by unqualified and inexperienced English teachers. This is in line with the teachers and lecturers law No. 14, 2005 which states that one of main duties of professional teachers is assessment. Therefore, this paper seems to be useful to improve their knowledge and understanding in assessment to avoid and reduce their subjectivity in assessing this productive skill. This paper also describes how to assess speaking skill, definitions of assessment, speaking, measurement, evaluation and test, characteristics of assessment and measurement, the difference between traditional assessment and alternative assessment. Besides, several purposes of assessment are also described in the paper to improve teachers’ insight in this topic. Keywords: assessment, speaking, evaluation, measurement, and test